Pengaruh Profitabilitas, Struktur Aset, Dan Likuiditas Terhadap Struktur Modal - Grace Gardenia, Jonnardi (Jurnal Paradigma Akuntansi, 2021)
The purpose of this study is to analyze the effect of profitability, asset structure, and liquidity on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2019 period. This research was conducted by taking 220 samples of manufacturing companies listed on the IDX in the period of 2015-2019, using purposive sampling method and processed using the EViews 11 program. The result of partially test (t test) shows that the profitability and liquidity have significant effect on capital structure, meanwhile the asset structure has no significant effect on the capital structure.